A Newborn Screening Education Best Practices Framework: Development and Adoption - Adrianna Evans; Keri LeBlanc; Natasha Bonhomme; Scott M. Shone; Amy Gaviglio; Debra Freedenberg; Jeremy Penn; Carol Johnson; Beth Vogel; Siobhan M. Dolan; Aaron J. Goldenberg (MDPI AG, 2019)
Newborn screening is a process-based public health service. Newborn screening staff and families alike are essential to maintaining the timeliness of the screening process. Newborn screening education must be accurate and accessible. Past newborn screening conferences have highlighted gaps in best practice and evidence-based guidance on newborn screening education. Sharing successful strategies across programs mitigates the scarcity of resources by cutting costs and reducing the burden of work. These factors illustrate the need for an education framework to guide newborn screening education efforts. The Newborn Screening Education Best Practices Framework responds to these issues by outlining guidance for newborn screening education approaches. Experts in the fields of newborn screening, genetics, and bioethics as well as previous research on best practice guidelines have contributed to the development of this framework. The framework outlines a process for users to evaluate newborn screening education approaches as best practices. This framework reviews best practices using a two-step approach, looking at guiding questions, implementation of the newborn screening issue, and evaluation. The framework helps the user define the characteristics of the newborn screening issue, intended audience, and practical steps to implementation, and then decide whether or not it can be used as a best practice.